Effectiveness of the novel 3D PreemieScanner for preterm infants’ growth monitoring confirmed in a simulated setting - Ronald H. J. van Gils; Ronald H. J. van Gils; Ronald H. J. van Gils; Ronald H. J. van Gils; Ronald H. J. van Gils; Onno K. Helder; Onno K. Helder; René F. Kornelisse; Timothy M. S. Singowikromo; Irwin Reiss; Jenny Dankelman (Frontiers in Medical Technology)
IntroductionPreterm infants’ growth is typically monitored through weight, body length (BL) and head circumference (HC). However, 3D cranial volume (CrV) is considered a more accurate indicator of brain growth than 2D HC. The PreemieScanner is a novel 3D measuring device that simultaneously measures BL, HC and CrV. Its clinical usability was tested in a simulated NICU setting.Materials and methodsThree extremely low birth weight (ELBW; BW < 1,000 gram) dolls with Optiflow breathing systems, (tubes positioned either at the front or back of the head) were used. Nurses conducted scan sessions and marked anatomical landmarks on 3D PreemieScanner images. As control, nurses measured HC manually with a standard measuring tape. Key outcomes were: (1) Measurement success rate, (2) Precision—percentage within clinically allowed limits, ±0.4 cm for BL, ±0.3 cm for HC, ±12 ml for CrV, and 3) accuracy—mean or median measurement error (MME) relative to the ground truth.ResultsThirty-five scan sessions resulted in 100% successful measurements for BL and HC; 80% for CrV. BL MME −3.3% (p < 0.001); 40% (42/105) within precision limits. HC MME (Optiflow-front) 0.0% (p = 0.63); 89% (51/57) within limits. HC MME (Optiflow-back) −0.4% (p = 0.91). 93% (43/46) within limits. MME HC measuring tape, (Optiflow-front) −0.8% (p < 0.001), 88% (50/57) within limits, and MME (Optiflow-back) −1.1% (p < 0.001), 83% (40/48) within limits. MME CrV (Optiflow-front) −1.8% (p = 0.01), 86% (31/36) within limits, MME CrV (Optiflow-back) −1.3% (p < 0.001), 98% (45/46) within limits.ConclusionsThe PreemieScanner is a reliable, comprehensive device for measuring BL, HC and CrV in ELBW infants. It integrates smoothly into routine care with minimal disturbance. HC measurements demonstrated higher accuracy and precision than traditional tape method. CrV measurements, with 93% within precision limits, can be regarded as acceptable, enabling development of CrV growth reference charts, enhancing clinical growth monitoring.